2020
DOI: 10.5937/selsem2002007n
|View full text |Cite
|
Sign up to set email alerts
|

Grain properties of yellow and red kernel maize hybrids from Serbia

Abstract: Physical traits, kernel structure and chemical composition of five yellow and five red kernel maize hybrids were the subjects of this study. The 1000-kernel weight, a physical indicator of grain quality, ranged from 325.76±7.47 g (ZP 555 red) to 375.63±4.18 g (ZP 606). The hard endosperm fraction content varied between 57.66±0.93% (ZP 4007) and 67.08±0.42% (ZP 366 red). Regarding chemical composition, starch was predominant constituent ranging from 66.80±0.18 (ZP 4007 red) to 72.96±0.37 (ZP 606). The highest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…inbred lines, some of which may be used in the breeding processes to get high-oil hybrids, in contrast to standard maize hybrids that are commercially used in flour production. The basic chemical composition of the analyzed wholegrain maize flours is mainly in accordance with previously published findings (Milašinović-Šeremešić et al, 2019;Nikolić, Božinović, Vančetović, Radosavljević Žilić, 2020). Maize protein solubility is an important functional characteristic that affects both the nutritional value and the utilizable value of maize grains.…”
Section: O N L I N E F I R S Tsupporting
confidence: 88%
“…inbred lines, some of which may be used in the breeding processes to get high-oil hybrids, in contrast to standard maize hybrids that are commercially used in flour production. The basic chemical composition of the analyzed wholegrain maize flours is mainly in accordance with previously published findings (Milašinović-Šeremešić et al, 2019;Nikolić, Božinović, Vančetović, Radosavljević Žilić, 2020). Maize protein solubility is an important functional characteristic that affects both the nutritional value and the utilizable value of maize grains.…”
Section: O N L I N E F I R S Tsupporting
confidence: 88%
“…All three axes cumulatively captured 79 .690% of the variability (Tables 4 and 5) . Depending on the genetic background and environmental conditions during the production, maize grain, on average, contains 54 -74% starch, 8 -14% protein, 3 -6% oil, and 1 .5 -3% crude fiber (Eckoff et al ., 2009, Nikolić et al ., 2020 . PC analysis for the basic chemical composition of the kernel showed that the examined hybrids which were grown in 2013 (5) stood out for their extremely low total protein content (extremely negative values of the PCA1 score) (Figure 4a) .…”
Section: Resultsmentioning
confidence: 99%
“…A significant hybrid x year interaction is found for all kernel characteristics (Harrelson et al 2019). Correlation between kernel properties depends on genotype, environment, and analysis technique in a laboratory (Nikolic et al 2020).…”
Section: Correlation Between Kernel Morphology and Corn Flour Fractionsmentioning
confidence: 89%